Clinico-radiological correlation and surgical outcome of idiopathic spinal cord herniation: A single centre retrospective case series. (4th May 2021) - Menon, Deepak; Nair, Sruthi S.; Thomas, Bejoy; Krishna Kumar, K.; Nair, Muralidharan
Abstract : Context: Idiopathic spinal cord herniation (ISCH) remains an obscure, under recognised but potentially treatable entity among the etiologies of compressive myelopathy. Findings: Here, we present a retrospective case series of eight patients of ISCH with their clinical features, imaging findings and long-term follow up data along with a relevant review of the literature. Mean age at presentation was 36 years with the duration of symptoms ranging from two months to more than thirty years. Contrary to existing data, only two patients in our series had the classical presentation of Brown-Sequard syndrome ( n  = 2). The clinical spectrum of the presentation was broad with pure spastic quadriparesis ( n  = 3), girdle sensation ( n  = 1) and radiculopathy ( n  = 1), the latter presentation has been unreported for ISCH. The typical radiological picture was seen in all patients. All except one patient was managed conservatively. In the one patient who underwent bilateral dentate ligament excision, there was mild functional improvement on long-term follow-up despite a definite worsening of the radiological picture. Five of the patients had a long-term follow-up with no clinically or functionally significant worsening. Clinical relevance: The current study highlights the wide clinical spectrum and relatively stable natural course of ISCH and reports on hitherto undescribed presentation as radiculopathy.